2006
DOI: 10.1536/ihj.47.159
|View full text |Cite
|
Sign up to set email alerts
|

<b>Poststenting Axial Redistribution of Atherosclerotic Plaque Into the Reference Segments and Lumen Reduction at the Stent Edge</b>

Abstract: SUMMARYLumen enlargement during coronary stenting results from vessel expansion and axial redistribution of atheromatous plaque along the stented segment and proximal and distal reference segments. Plaque burden predicts stenosis at the stent edge. The aim of this study was to investigate the fate of shifted plaque with special reference to whether or not plaque shift (PSh) correlates with late lumen reduction. This is a prospective study conducted on 54 consecutive patients who underwent bare metal stenting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, more detailed studies analysis have shown that the last mechanism is more complex [ 23 , 24 ]. It consists of the axial redistribution of atheromatous plaque [ 25 , 26 ] and plaque compression [ 23 ] rather than embolization [ 27 ]. Previous IVUS studies have demonstrated that in non-calcific lesions, the mechanisms of the lumen enlargement after stenting (direct implantation or after predilatation) are significantly influenced by atherosclerotic remodeling, plaque eccentricity and plaque composition [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more detailed studies analysis have shown that the last mechanism is more complex [ 23 , 24 ]. It consists of the axial redistribution of atheromatous plaque [ 25 , 26 ] and plaque compression [ 23 ] rather than embolization [ 27 ]. Previous IVUS studies have demonstrated that in non-calcific lesions, the mechanisms of the lumen enlargement after stenting (direct implantation or after predilatation) are significantly influenced by atherosclerotic remodeling, plaque eccentricity and plaque composition [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, vessel and lumen areas increased equally, while the plaque area decreased after stent deployment [ 24 ]. Algowhary et al [ 25 ] showed axial redistribution of atheromatous plaque along the segment and proximal and distal reference segments. Prati et al [ 27 ] found that the decrease in the plaque area during stenting predicts CK-MB release suggesting a high association between stenting and plaque embolization in patients with unstable angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
“…Initial IVUS studies conducted in patients with SCAD demonstrated that stent implantation redistributed plaque longitudinally across the vessel to the proximal and distal edges of the stent with the potential for release of plaque debris into coronary circulation [7][8][9]. NIRS imaging alone confirmed a lipidic component of these findings [14].…”
Section: Discussionmentioning
confidence: 99%
“…NIRS-IVUS studies demonstrated that lipidrich plaques might be prone to distal embolization after stenting because of redistribution of lipidic plaque and release of its debris into circulation [7][8][9]. Indeed, stenting of lipid-rich lesions increases the risk of periprocedural myocardial infarction suggesting that plaque redistribution is related to composition and morphology [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been proposed, including plaque shift, the snow-plow effect, and stent jailing of the side branch. 1,12,13) An acute occlusive side branch during PCI has been shown to have a good prognosis. 14,15) The patency of the side branch is often well maintained at long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%